A Case of Myasthenia Gravis and Stiff‐Person Syndrome That Improved After Extended Thymectomy - Shoji Okado; Tetsuya Mizuno; Yuta Kawasumi; Yuka Kadomatsu; Toyofumi Fengshi Chen‐Yoshikawa (Respirology Case Reports)
ABSTRACT In cases of thymoma with autoimmune disease, extended thymectomy may improve disease symptoms and medication effects. Myasthenia gravis (MG) is the most common complication, but thymoma with Stiff‐Person syndrome (SPS) is rare, and there are few reports of surgery. In the present case, we performed robot‐assisted extended thymectomy on a 74‐year‐old man with thymoma who had MG and SPS. At 6 months after surgery, his MG and SPS symptoms had improved and the dose of prednisolone had been reduced, confirming that surgical treatment contributed to disease control. Thus far, only two studies have been published on thymoma surgery in conjunction with MG and SPS, and both have documented the progression of neurological symptoms after surgery. To the best of our knowledge, this is the first report of a resected thymoma with MG and SPS, both of which were controlled after surgery.